Global Transformations in the Life Sciences, 1945-1980 - Savelli, Mat, 1982-; Manning, Patrick, 1941- (Book collections on Project MUSE., 2018)
The second half of the twentieth century brought extraordinary transformations in knowledge and practice of the life sciences. In an era of decolonization, mass social welfare policies, and the formation of new international institutions such as UNESCO and the WHO, monumental advances were made in both theoretical and practical applications of the life sciences, including the discovery of life's molecular processes and substantive improvements in global public health and medicine. Combining perspectives from the history of science and world history, this volume examines the impact of major world-historical processes of the postwar period on the evolution of the life sciences. Contributors consider the long-term evolution of scientific practice, research, and innovation across a range of fields and subfields in the life sciences, and in the context of Cold War anxieties and ambitions. Together, they examine how the formation of international organizations and global research programs allowed for transnational exchange and cooperation, but in a period rife with competition and nationalist interests, which influenced dramatic changes in the field as the postcolonial world order unfolded.